ANALISIS PEMBINAAN PRESTASI SISWA EKSTRAKURIKULER BOLA VOLI SMP NEGERI 5 BANYUASIN III - Nomansyah, Amar Nopta Nomansyah Amar Nopta; Junaidi, Ilham Arvan; Mahendra, Agung; Kumbara, Hengki (STKIP Melawi, 2024)
Abstract: The aim of the research is to analyze the process of developing volleyball extracurricular student achievement at SMP Negeri 5 Banyuasin III. The research method is a qualitative descriptive method. The object of the research was extracurricular volleyball students at SMP Negeri 5 Banyuasin III. Data collection used observation triangulation, guided interviews and documentation. Data analysis was carried out qualitatively through reduction, data presentation and drawing conclusions. The results of this research are that the management of volleyball performance development at SMP Negeri 5 Banyuasin III is running but in several aspects it has not been fulfilled, for example in the aspects of infrastructure, training and training programs, both from planning, organizing, actuating and controlling. In the aspect of training facilities, the school has planned but at the implementation stage the infrastructure has not been met, considering that this aspect is quite difficult to realize because it is related to the budget. The training aspect and training program is that the trainer has planned to prepare a training program, but it has not been realized due to several obstacles. Keywords: Volleyball Achievement Development Abstrak: Tujuan penelitian adalah untuk menganalisis proses pembinaan prestasi siswa ekstrakurikuler bola voli di SMP Negeri 5 Banyuasin III. Metode penelitian merupakan metode deskriptif kualitatif. Objek penelitian adalah siswa ekstrakurikuler bola voli SMP Negeri 5 Banyuasin III. Pengumpulan data menggunakan tringulasi observasi, wawancara terpimpin dan dokumentasi. Analisis data dilakukan secara kualittatif melalui reduksi, penyajian data dan penarikan Kesimpulan. Hasil penelitian ini bahwa manajemen pembinaan prestasi bola voli di SMP Negeri 5 Banyuasin III berjalan tetapi pada beberapa aspek belum terpenuhi, misalnya pada aspek sarana prasarana, latihan dan program latihan, baik dari planning, organizing, actuating dan controling. Pada aspek sarana latihan, dimana sekolah telah merencanakan tetapi pada tahap pelaksanaanya sarana prasarana belum terpenuhi, mengingat aspek ini cukup berat untuk direalisasikan karena berkaitan dengan anggaran. Aspek latihan dan program latihan hakikatnya pelatih telah merencanakan penyusunan program latihan, tetapi tidak terealisasi karena beberapa kendala. Kata Kunci: Pembinaan Prestasi Bolavoli